Strategi Pemasaran Cabai Merah Pada Sub Terminal Agribisnis Manik Mekar Nadi - NI NYOMAN TISNA DEWI; I NYOMAN GEDE USTRIYANA; A.A.A. WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
The Marketing Strategies of Red Chili at Sub Terminal AgribusinessManik Mekar NadiRed chili is one type of commercial vegetable that has long been cultivated in Indonesia. STA Manik Mekar Nadi has implemented marketing strategies to market its agricultural production, especially red chili. The purpose of the study was to analyze the internal and external factors, as well as the right strategies to be carried out by STA Manik Mekar Nadi in the marketing of red chili. The choice of location was done purposively and the number of the key informants was seven peoples. Results of research of marketing strategies of red chili showed that the internal factors include: the strength factors, namely, its strategic location, complete facilities, regular customers, and the guaranteed quality of red chili, while the weakness factors, namely, lack of capital, perishable products, unable to meet the demand, not using the services / advertising in the mass media. External factors include: opportunity factors, namely increasing purchasing power of consumers, government supports, increased domestic market demand, and technological development support, while the threat factors, namely, the emergence of new similar competition, consumers ‘sensitivity to price changes, fluctuations in the price of red chili at the local farmers, and the stronger bargaining power of consumers. The strategies adopted by STA Manik Mekar Nadi in marketing the red chili are to maintain the quality of red chili, to expand markets and product distribution, to increase the production of red chili, to have capital loans, promotion of technology, product standardization, standardization of prices, to expand business networks, to increase operational facilities, to maintain the stability of prices at the consumer level, and to increase the stock of red chili. The STA Manik Mekar Nadi is recommended to apply for financial assistance to the government, to add transportation and to enlarge the warehouse, as well as to conduct promotion.